Heidegger and Stiegler on failure and technology. Issue 4 (20th March 2020) - Irwin, Ruth
Abstract: Heidegger argues that modern technology is quantifiably different from all earlier periods because of a shift in ethos from in situ craftwork to globalised production and storage at the behest of consumerism. He argues that this shift in technology has fundamentally shaped our epistemology, and it is almost impossible to comprehend anything outside the technological enframing of knowledge. The exception is when something breaks down, and the fault 'shows up' in fresh ways. Stiegler has several important addendums to Heidegger's thesis. Heidegger fails to fully appreciate the early Greek myth of Prometheus, and the technological depth that fire offers all human societies. The fall, or failure, is doubled in the myth of Prometheus, and is at the root of all cultures. Since the onset of Information Technology, the acceleration of life is disorientating our Being. I argue the fall in both Heidegger and Stiegler has encaptured their imagination. Education is vital for generating the imaginary, along with the ability to think critically, and ensures the authenticity of political processes, but as importantly, it helps us to imagine the future beyond the Armaggedon scenarios of climate change, and ecological devastation. The Arts and Humanities are at the core of generating a new future.